Muscle Excitability Scale for the assessment of spastic reflexes in spinal cord injury: development and evaluation - Kriz, Jiri; Nasincova, Zuzana; Gallusova, Veronika; Vyskocil, Tomas; Gregor, Martin; Slaby, Krystof; Sediva, Kristyna (Spinal cord, 2024)
STUDY DESIGN: A psychometric study. OBJECTIVES: To introduce a novel simple tool designed to evaluate the intensity of the phasic (dynamic) component of spastic motor behavior in spinal cord injury (SCI) people and to assess its reliability and validity. SETTING: The study was developed in the Spinal Cord Unit at University Hospital Motol and Paraple Centre in Prague, Czech Republic. METHODS: The Muscle Excitability Scale (MES) is designed to rate muscle motor response to exteroceptive and proprioceptive stimuli. The impairment rating ranges from zero muscle/muscle group spasm or clonus to generalized spastic response. The selected 0 to 4 scale allows for comparing the MES results with those of the Modified Ashworth Scale (MAS). After long-term use and repeated revisions, a psychometric analysis was conducted. According to the algorithm, two physiotherapists examined 50 individuals in the chronic stage after SCI. RESULTS: The inter-rater reliability of MES for both legs showed κ = 0.52. The intra-rater reliability of MES for both legs showed κ = 0.50. The inter-rater reliability of simultaneously assessed MAS for both legs was higher, with κ = 0.69. The intra-rater reliability of MAS for both legs showed κ = 0.72. Spearman's rank correlation coefficient between MES and spasm frequency of Penn Spasm Frequency Scale (PSFS) was low, while the correlation coefficient between MES and the severity part of PSFS was moderate. CONCLUSIONS: The MES is a complementary tool for assessing the dynamic component of spastic motor behavior in SCI people. It allows a more comprehensive clinical characterization of spastic reflexes when used along with the MAS.
Keywords: dospělí; kosterní svaly; Female; Psychometrics; psychometrie; Adult; mladý dospělý; ženské pohlaví; Reproducibility of Results; lidé; poranění míchy; Muscle, Skeletal; stupeň závažnosti nemoci; Muscle Spasticity; reprodukovatelnost výsledků; Spinal Cord Injuries; Male; Aged; Young Adult; lidé středního věku; senioři; mužské pohlaví; Severity of Illness Index; svalová spasticita; Middle Aged; Humans